Exploring the Impact of the Show and Tell Method on Student Engagement in Maharah Kalam - Adilah Zharifah; Amrulloh, Muhammad Afif; Zulhannan, Zulhannan; Wahidah, Yeni Lailatul (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
This study investigates the effectiveness of the Show and Tell method in improving the Maharah Kalam skills of grade X students of MAN 2 Bandar Lampung. Using Classroom Action Research (PTK) and a mixed method approach (70% quantitative, 30% qualitative), this study collected quantitative data through oral tests of Maharah Kalam at the pre-action stage until cycle 2 to measure the numerical improvement of students' speaking ability. Qualitative data, obtained through observation and descriptive questionnaires, was used to understand more deeply the perceptions and reasons behind students' interest in learning. The results showed significant improvement in Maharah Kalam proficiency, as evidenced by the increase in the average score of the oral test from pre-action to cycle 2. The qualitative data provided context that reinforced these quantitative findings, explaining how Show and Tell impacted on students' motivation, confidence and interaction in learning Maharah Kalam. This study concludes that Show and Tell is an effective learning alternative to improve students' Arabic speaking skills.